A Dual-layered Microfluidic System for Long-term Controlled In Situ Delivery of Multiple Anti-inflammatory Factors for Chronic Neural Applications. - Frey, Laura (Adv Funct Mater, 2017)
We report the development of a microfluidic system capable of repeated infusions of anti-inflammatory factors post-implantation for use as a coating for neural probes. This system consists of a microchannel in a thin gelatin methacryloyl (GelMA)-polyethylene glycol (PEG) composite hydrogel surrounded by a porous polydimethylsiloxane (PDMS) membrane, where the hydrogel can be dried to increase the stiffness for easy insertion. Reswelling allowed us to perfuse interleukin (IL)-4 and dexamethasone (DEX) as anti-inflammatory factors through the channel with minimal burst release and significant amounts of IL-4 were observed to release for up to 96 hr post-infusion. Repeated injections of IL-4 increased the ratio of prohealing M2 versus proinflammatory M1 phenotypes of macrophages encapsulated in the hydrogel by six fold compared with a single injection, over a 2-week period. These repeated infusions also significantly downregulated the expression of inflammatory markers tumor necrosis factor (TNF)-α and IL-6 in astrocytes encapsulated in hydrogel. To demonstrate the system as a coating of neural probe for in vivo applications, we further fabricated a prototype device, where a thin dual-layered microfluidic system was integrated onto a metal probe. Such a drug delivery system could help reduce the formation of a glial scar around neural probes.